2009
DOI: 10.1088/1468-6996/10/3/034603
|View full text |Cite
|
Sign up to set email alerts
|

SNP genotyping by DNA photoligation: application to SNP detection of genes from food crops

Abstract: We describe a simple and inexpensive single-nucleotide polymorphism (SNP) typing method, using DNA photoligation with 5-carboxyvinyl-2 -deoxyuridine and two fluorophores. This SNP-typing method facilitates qualitative determination of genes from indica and japonica rice, and showed a high degree of single nucleotide specificity up to 10 000. This method can be used in the SNP typing of actual genomic DNA samples from food crops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…None of these OTR-based DNA chips require any enzymes or time-consuming steps, as opposed to most conventional SNP detection systems (such as RT-PCR and traditional SNP arrays). In addition, the bio-orthogonal photo-reversibility of the ODNs containing CV U, allows for recycling of the DNA chip, further reducing the cost of testing [49]. Therefore, these platforms present significant advantages over solution-based OTRs and conventional SNP detection methods (such as RT-PCR and SNP arrays).…”
Section: Otrs On Glass Surfacesmentioning
confidence: 99%
“…None of these OTR-based DNA chips require any enzymes or time-consuming steps, as opposed to most conventional SNP detection systems (such as RT-PCR and traditional SNP arrays). In addition, the bio-orthogonal photo-reversibility of the ODNs containing CV U, allows for recycling of the DNA chip, further reducing the cost of testing [49]. Therefore, these platforms present significant advantages over solution-based OTRs and conventional SNP detection methods (such as RT-PCR and SNP arrays).…”
Section: Otrs On Glass Surfacesmentioning
confidence: 99%
“…Thus, there is an ever-increasing need for a reliable, low-cost, highthroughput standardized assay that can quickly and accurately screen for SNPs. 10 Many previous studies have reported on the immobilization of single-stranded DNA (ssDNA) probe molecules onto a chemically modified surface and the detection of double-stranded DNA (dsDNA) hybridization with target DNA molecules. Microarrays require the immobilization of probe ssDNA onto a chemically treated surface with strong selectivity and high specificity.…”
Section: Introductionmentioning
confidence: 99%